Strategies For Teacher Excellence In The 21st Century Education Era: Integration Of Technology, Curriculum, And Multidisciplinary Teaching In Elementary Schools - Siminto, Siminto; Imelda , Imelda; Rina Setyaningsih; Didik Cahyono; Azwar Rahmat (IJGIE (International Journal of Graduate of Islamic Education), 2024)
This research aims to explore and identify effective pedagogical strategies in the dynamic context of basic education in the 21st era, with a focus on the integration of technology, curriculum and multidisciplinary teaching approaches. In response to changing educational needs, this study examines how technology can be applied by educators to improve curriculum delivery and facilitate multidisciplinary learning that combines various subjects in harmony. This research involved an in-depth literature review and analysis of case studies from various primary schools to uncover best practices and challenges faced in their implementation. The primary focus is on how this holistic approach impacts student engagement and their learning outcomes, as well as ways to empower teachers in an ever-evolving educational environment. The findings from this study provide important insights into teacher excellence in the 21st century, offering recommendations for educators, policymakers, and researchers in efforts to improve the quality of basic education. The results of this study contribute significantly to the discourse of teacher excellence and 21st century education, highlighting the importance of responsive and innovative educational adaptations in elementary schools.